KESIAPAN GURU MADRASAH DI KOTA SEMARANG DALAM MENGHADAPI PELAKSANAAN PPG - Amin Farikh (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2015)
AbstractProfessional Teacher Education (PTE/ PPG) can be regarded as a program to improve the competence of today’s most important teacher. This program is not solely the learning process of the teachers, but also as a starting point increase teachers’ welfare through the provision of teaching certi" cate and allowances. However, the level of preparedness of teachers to plan the holding of Professional Teacher Education (PTE/ PPG) is still low. The mechanism and all the provisions of the Professional Teacher Education (PTE/ PPG) is not understanded, the teacher could not prepare him to adapt. Therefore, the implementation of Professional Teacher Educationshould involve at least four (4) It is important to note ; First, Improved readiness and support of teachers. Second, socialization widely. Third, the accuracy of the allocation of time. Fourth, the full support of the government. If the four components are met then automatically readiness of teachers on the implementation of Professional Teacher Education (PTE/ PPG) will go well.